การปฏิบัติงานของผู้บริหารที่ส่งผลต่อประสิทธิผลของสถานศึกษา สังกัดสำนักงานเขตพื้นที่การศึกษา ประถมศึกษาสุพรรณบุรี เขต 2 - อุดมผล ประไพ; วังถนอมศักดิ์ มัทนา (วารสารการบริหารการศึกษา มหาวิทยาลัยศิลปากร, 2016)
การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อทราบ 1) การปฏิบัติงานของผู้บริหารสถานศึกษา สังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาสุพรรณบุรีเขต 2 2) ประสิทธิผลของสถานศึกษาสังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาสุพรรณบุรี เขต 2และ 3) การปฏิบัติงานของผู้บริหารสถานศึกษาที่ส่งผลต่อประสิทธิผลของสถานศึกษาสังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาสุพรรณบุรี เขต 2 กลุ่มตัวอย่างได้แก่ สถานศึกษาสังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาสุพรรณบุรี เขต 2 จำนวน 103 โรงเรียน ผู้ให้ข้อมูลโรงเรียนละ 4 คน รวมจำนวน 412 คน เครื่องมือที่ใช้เป็นแบบสอบถามเกี่ยวกับการปฏิบัติงานของผู้บริหารสถานศึกษาตามมาตรฐานของสำนักงานเลขาธิการคุรุสภาแลประสิทธิผลของสถานศึกษาตามแนวคิดของฮอยและมิสเกล สถิติที่ใช้ในการวิเคราะห์ข้อมูล คือ ความถี่ ร้อยละ มัชฌิมเลขคณิต ส่วนเบี่ยงเบนมาตรฐาน และการวิเคราะห์การถดถอยพหุคูณแบบขั้นตอน ผลการวิจัยพบว่า 1. การปฏิบัติงานของผู้บริหารสถานศึกษาสังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาสุพรรณบุรี เขต 2 ในภาพ รวมและรายด้านอยู่ในระดับมาก 2. ประสิทธิผลของสถานศึกษา สังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาสุพรรณบุรี เขต 2 โดยภาพรวม และรายด้านอยู่ในระดับมาก 3. การปฏิบัติงานของผู้บริหารส่งผลต่อประสิทธิผลของสถานศึกษา สังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษา สุพรรณบุรี เขต 2 อย่างมีนัยสำคัญทางสถิติที่ระดับ .05 THE ADMINISTRATORS’ JOB PERFORMANCE AFFECTING THE EFFECTIVENESS OF SCHOOLS UNDER SUPHANBURI PRIMARY EDUCATIONAL SERVICE AREA OFFICE 2. The purposes of this research were to find 1) the school administrators’ job performance under Suphanburi Primary Educational Service Area Office 2, 2) the effectiveness of schools under Suphanburi Primary Educational Service Area Office 2, and 3) the school administrators’ job performance affecting the effectiveness of schools under Suphanburi Primary Educational Service Area Office 2. The sample used in this research were 103 schools under Suphanburi Primary Educational Service Area Office 2. There were 4 respondents from each school; with the total respodents of 412. The research instrument was a questionnaire regarding the school administrators’ job performance according to the professional standards of The Secretariat Office of The Teachers’ Council and the school effectiveness based on Hoy and Miskel’s concept. The statistics used to analyze the data were frequency, percentage, arithmetic mean, standard deviation, and stepwise multiple regression analysis. The findings of the research were as follow: 1.The school administrators’ job performance under Suphanburi Primary Educational Service Area Office 2, as a whole and as an individual, was found at a high level. 2.The effectiveness of schools under Suphanburi Primary Educational Service Area Office 2, as a whole and as an individual, was found at a high level. 3.The school administrators’ job performance affected the effectiveness of schools under Suphanburi Primary Educational Service Area Office 2, was at a .05 level of statistical significance.